Bone density in apheresis donors and whole blood donors. Issue 4 (29th May 2015) - Boot, C. L.; Luken, J. S.; van den Burg, P. J. M.; de Kort, W. L. A. M.; Koopman, M. M. W.; Vrielink, H.; van Schoor, N. M.; den Heijer, M.; Lips, P.
<x xml:space="preserve">Abstract</x> Apheresis donation using citrate causes acute decrease in serum calcium and increase in serum parathyroid hormone. Long‐term consequences, such as decrease in bone mineral density (BMD), are not known. In this study, we compared the BMD of 20 postmenopausal apheresis donors (mean donation number 115 times in up to 15 years) with that of 20 whole blood donors (for 15 years or more) aged 55–70. BMD in the lumbar spine was not lower in apheresis donors than in blood donors (mean ± SD 1·00 ± 0·18 vs. 0·92 ± 0·12, P = 0·09). In the hip, BMD was not different between the groups.